A Note on Solymosi’s Sum-Product Estimate for Ordered Fields - Xue, Boqing (Ukrains’kyi Matematychnyi Zhurnal, 2014)
It is proved that Solymosi’s sum-product estimate max{|A + A|, |A · A|} ≫ |A|4/3/(log |A|)1/3 holds for any finite set A in an ordered field F.